Planning & scheduling by using Microsoft Project a case study of "suggestion for construction and completion the Science Department for University Islam Antarabangsa Malaysia, Bandar Indera Mahkota, Kuantan, Pahang" - Mohd Johari, Othman (2006)
The construction industry is significant in the development of the Malaysian economy towards its realization of achieving vision 2020 to attain the status of a fully developed nation. To implement construction project, a proper planning and scheduling is of vital important in order for the project to be executed and run smoothly. The best schedule is not the schedule showing the project completed in the shortest time period, it is the schedule that meets the primary objectives of the total project. Those primary objectives are to create a quality project, completed on time, within budget, and in a safe work environment. Therefore, the focus of this research is to conduct and exploratory study on developing planning and scheduling in construction project. To achieve the aim of the study, the following objectives has been identified such as to study the concept of planning and scheduling in construction project, to study the construction sequence of work for multi storey building and to produce S-Curve by application of Microsoft Project software. Two multi storey building project was selected and structured interview was conducted to experience personal who really involved in the construction project such as Project Manager, Planner Engineer and Project Engineer. The study has been carried out using case study method in which two samples of construction schedule has been evaluated and analyze in term on how to develop the scheduling. From the study, it was found on how the project was planned, the sequence of work and linking relationships between activities for the whole project. By choosing the best schedule of the project, then new schedule has been developed by using Microsoft Project 2003 until produce the S-Curve. In conclusion, no doubt that information from the research can benefit both the practiced and the education of project.